The Influence Of Celebrity Endorsers And Price On The Decision To Purchase Elzatta Hijabs (A Case Study Of Elzatta Store Customers In Lahat City) - Tania Putri Rahmadhani Gianto; Emila Sholiha; Markus Markus (Journal of Management, Economic, and Accounting, 2026)
This study aims to determine the Influence of Celebrity Endorsers and Prices on Elzatta Hijab Purchase Decisions (Case Study of Elzatta Shop Customers in Lahat City) partially or simultaneously. This study is a quantitative associative research using the Accidental Sampling technique and the Slovin formula method in determining the sample. The sample used in this study amounted to 81 people who were used as research respondents. Based on the results of the study, the regression equation Y = 4.602 + 0.385 X1 + 0.503 X2 + e, means that without the variables Celebrity Endor (X1) and Price (X2), then the Purchase Decision (Y) is 4.602. The value of the determination coefficient (R2) is 0.551, meaning that the independent variables have a contribution with dependent variables of 55.1% and the remaining 44.9% are influenced by other factors that were not studied by the author. Based on the results of SPSS processing version 25.0, the Fcal value of 47.876 was obtained while the Ftable value was 3.114 thus 47.876 > 3.114, Ho was rejected and Ha was accepted, meaning that the variables Celebrity Endor (X1) and Price (X2) together had a significant effect on the Decision Purchase (Y). The Ttable value is 1.664. By comparing the value of Thitung and Ttabel it can be concluded: the variable Celebrity Endorser (X1) with the value of Tcount > Ttable or 4.664 > 1.664 , then Ho is rejected and Ha is accepted. Price (X2) with a Thcal value of > Ttable or 6,270 > 1,664, then the variables Celebrity Endorser (X1) and Price (X2) have a partial effect on the Purchase Decision (Y) of Elzatta Hijab (Case Study of Elzatta Store Customers in Lahat City).